ON SPECTRAL PROPERTIES OF A BOUNDARY VALUE PROBLEM OF THE FIRST ORDER EQUATION WITH DEVIATING ARGUMENT - A.Sh. Shaldanbayev; S.M. Shalenova; M.B. Ivanova; A.A. Shaldanbayeva (Academic Scientific Journal of Computer Science, 2019)
In this paper, we study spectral properties of a boundary value problem of a first order differential equation with constant coefficients and deviating argument; the deviation is present at the highest term of the equation, and it cannot be transferred to the lower terms of the equation without an additional condition. By spectral properties, we mean completeness and basic properties of a system of eigenfunctions and associated functions of a boundary value problem, as well as Volterra properties.